Genotypic Variation in Physico-Chemical Properties of Avocado at Dailekh - Luitel, Binod Prasad (Nepal Journal of Science and Technology, 2022)
This study was conducted to analyze the physical and chemical properties of the fruits in 16 avocado genotypes in 2020. Fruits were harvested at physiological maturity stage from seed propagated plants and analyzed their physical (fruit weight, fruit length, fruit diameter, pulp weight, pulp/fruit ratio, and seed/fruit ratio) and chemical properties (moisture content, reducing sugar, total soluble solids, crude protein, total ash, phosphorous, iron, calcium, crude fat and crude fiber). The analysis of one-way variance of the data revealed highly significant variation in physico-chemical properties among avocado genotypes. Genotypes HRSDAV05, HRSDAV07, HRSDAV06 and HRDAV03 displayed the lowest seed/fruit ratio of 10.0, 13.5, 14.6 and 16.8%, respectively. Total soluble solid (TSS) content was the highest in HRSDAV08 (6.7 °Brix), HRSDAV03 (6.0 °Brix), HRSDAV07 (6.0 °Brix) and HRSDAV012 (6.0 °Brix). Crude protein was the highest in HRSDAV07 (19.2%), HRSDAV09 (17.8%) and HRSDAV014 (17.4%). HRSDAV03 and HRSDAV012 had the highest total ash content of 6.4% and 5.1%, respectively. Phosphorus content was the highest in HRSDAV03 (235.2 mg/100 g), but iron content was the highest in HRSDAV07 (2.5 mg/100 g). Crude fat and crude fiber were the highest in HRSDAV013 (63.0%) and HRSDAV03 (48.4%), respectively. The analysis of physico-chemical characters of avocado fruits identified HRSDAV03, HRSDAV05, HRSDAV06, HRSDAV07, HRSDAV08, HRSDAV09 and HRSDAV013 as potential parental genotypes for developing new cultivars.